Front Cover: Structure–Activity and Structure–Toxicity Relationships of Peptoid‐Based Histone Deacetylase Inhibitors with Dual‐Stage Antiplasmodial Activity (ChemMedChem 9/2019). (6th May 2019) - Mackwitz, Marcel K. W.; Hesping, Eva; Antonova‐Koch, Yevgeniya; Diedrich, Daniela; Woldearegai, Tamirat Gebru; Skinner‐Adams, Tina; Clarke, Mary; Schöler, Andrea; Limbach, Laura; Kurz, Thomas; Winzeler, Elizabeth A.; Held, Jana; et al.
Abstract : The Front Cover illustrates hit compound2h which is active on Plasmodium falciparum ‐infected erythrocytes. A homology model of the putative P. falciparum histone deacetylase (HDAC) molecular target is shown in gold. The neglected disease malaria is responsible for over 400, 000 deaths each year, and P. falciparum is the most lethal of the human malaria parasites. Parasite resistance has been reported for all currently used antimalarial drugs, and new drugs are needed. In this work we present peptoid‐based HDAC inhibitors as novel compounds with potent dual‐stage antiplasmodial activity. Cover artwork by M. K. W. Mackwitz and E. Hesping. More information can be found in the Full Paper by Finn K. Hansen, Katherine T. Andrews et al. onpage 912 in Issue 9, 2019 (DOI:10.1002/cmdc.201800808 ).